2021
DOI: 10.3389/fneur.2021.602979
|View full text |Cite
|
Sign up to set email alerts
|

Use of Next-Generation Sequencing for the Molecular Diagnosis of 1,102 Patients With a Autosomal Optic Neuropathy

Abstract: Advances in next-generation sequencing (NGS) facilitate the diagnosis of genetic disorders. To evaluate its use for the molecular diagnosis of inherited optic neuropathy (ION), a blinding disease caused by the degeneration of retinal ganglion cells, we performed genetic analysis using targeted NGS of 22 already known and candidate genes in a cohort of 1,102 affected individuals. The panel design, library preparation, and sequencing reactions were performed using the Ion AmpliSeq technology. Pathogenic variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…In our cohort, OPA1 was responsible for seven probands (50% of probands with a genetic diagnosis of autosomal HON) and was the most common disease-causing gene. This percentage was similar to that observed in previous studies [ 15 , 21 ]. OPA1 contains 30 exons spread over 100 Kb of genomic DNA [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our cohort, OPA1 was responsible for seven probands (50% of probands with a genetic diagnosis of autosomal HON) and was the most common disease-causing gene. This percentage was similar to that observed in previous studies [ 15 , 21 ]. OPA1 contains 30 exons spread over 100 Kb of genomic DNA [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in this study, we focused on exploring autosomal HON with a panel-based NGS test containing 52 HON-associated genes. Recently, two large-scale NGS-based genetic surveys for HON have been published [ 14 , 15 ]. Although the numbers and ranges of the target genes differed, these studies have reported a detection rate of 22–40% in identifying the disease-causing variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Obtaining a genetic diagnosis in affected individuals can inform management, and clinical genomic testing is increasingly being used as a frontline diagnostic tool for these disorders. [3][4][5][6][7][8] Notably, the more widespread availability of gene-directed interventions including gene therapy and preimplantation genetic testing has increased both the value and risk of genomic testing. [9][10][11][12][13][14] This places substantial demands on the delivery of testing in a timely and accurate manner.…”
Section: Introductionmentioning
confidence: 99%